ANALYSIS OF MORAL VALUES IN THE CERITA CEKAK DJAKA LODANG MAGAZINE JUNE-SEPTEMBER 2022 EDITION - Khoirunnisa, Hasna; Setyowati, Herlina; Qurniawati, Zuly; Aryanto, Aris (Jurnal Ilmu Bahasa, Sastra dan Pengajarannya, 2024)
This study aims to describe the moral values and the relevance of moral values contained in cerkak or cerita cekak (short stories) of Djaka Lodang magazine in June-September edition of 2022. This research is a descriptive qualitative. The data source of this research is cerkak of Djaka Lodang magazine June-September edition of 2022 totaling 17 titles. The data collection technique of this research is done by using library technique, listening technique, and note-taking technique. The data validity technique uses semantic validity and observation persistence. The data analysis technique used content analysis technique. Based on the results of the analysis, it can be seen that moral values include moral values of human relationships with God, which the author found from the cerkak there are 4 indicators: surrender to God, feelings of sin to God, praying and begging to God, and recognizing God's greatness; moral values of human relationships with themselves, found 8 indicators: self-esteem, self-confidence, fear, longing, resentment, loneliness, self-responsibility, and courtesy; the moral value of human relations with humans in the social sphere, there are 5 indicators: helping others, true love, helping the weak selflessly, respecting each other, knowing each other; the moral value of human relations with nature, there are 2 indicators: protecting and preserving nature to avoid all disasters caused by human carelessness, and utilizing natural resources. Moral values in cerkak of Djaka Lodang magazine are still relevant to be applied in today's life.